Complete Mitochondrial Genomes Reveal Population-Level Patterns in the Widespread Red Alga Gelidiella fanii (Gelidiales, Rhodophyta) - Boo, Ga Hun; Zubia, Mayalen; Hughey, Jeffery R.; Sherwood, Alison R.; Fujii, Mutue T.; Boo, Sung Min; Miller, Kathy Ann (Frontiers in Marine Science, 2020)
Although complete mitogenomic data have been widely applied in human and other animal population studies, they are extremely limited for florideophycean red algal populations. Gelidiella fanii is a recently described rhodophyte, previously misidentified as G. acerosa, a cosmopolitan agar-yielding species from tropical to subtropical waters. To decipher patterns in genetic diversity and geographic distribution for G. fanii, we obtained 10 complete mitogenomes including two outgroups, G. acerosa and G. flabella. The mitogenomes ranged in size from 25,223 bp to 25,281 bp and had 48 genes, which are similar in general structure, gene order and content, and presence of a group II intron. Phylogenomic analysis revealed that G. fanii was monophyletic and clearly separate from G. acerosa. The range of G. fanii was extended from Southeast Asia and northern Australia to Eritrea, Juan de Nova Island, and Kenya in the west, and to Hawai‘i and Tetiaroa Atoll to the east. Haplotype network analysis of cox1 revealed seven geographically structured groups: Southeast Asia, Kenya/Juan de Nova Island, Indonesia, northern Australia, the Philippines, Tetiaroa Atoll, and Hawai‘i. This regional structure has likely resulted from the separation and isolation of an ancient widespread population during the Pleistocene. This study demonstrates that mitogenome sequencing is a powerful genotyping tool for studies of genetic diversity, biogeography, and conservation of economically valuable marine algal species.